Nursing of an elderly patient with hypertension treated with Traditional Chinese Medicine soaking bath (中药泡洗技术治疗老年高血压1例的护理) - LI Xu (李旭); YE Yun (叶云); CAO Fang (曹芳); TANG Ling (唐玲) (中西医结合护理, 2022)
This paper summarized the observation and nursing of an elderly patients with hypertension treated with Traditional Chinese Medicine (TCM) soaking bath technology during hospitalization. Nursing assessment, standard procedure and cautions of soaking bath, component analysis of Chinese herbal medicine, routine nursing interventions such as psychological care and dietary guidance were summarized. Under the guidance of the theory of TCM syndrome differentiation and nursing, TCM soaking bath technology is potentially effective to relieve the dizziness and headache symptoms in the elderly patient with hypertension. (本文总结1例老年高血压患者住院期间运用中药泡洗技术治疗的护理经验, 包括护理评估、中药泡洗操作方法、药方组成、注意事项以及心理护理、饮食护理等常规护理。基于中医辨证施护理论指导, 采取中药泡洗并辅以护理措施, 能有效缓解老年高血压患者头晕头痛症状, 稳定血压, 从而缓解病情。)